2004
DOI: 10.1177/104063870401600503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and Production Type on Liver Copper Concentrations in Calves

Abstract: Abstract.A retrospective study of necropsy reports was undertaken to assess the relation between liver copper concentration and age, sex, and production class for calves that did not have a history compatible with copper toxicosis or with copper deficiency. Results of a generalized least squares regression analysis of 601 records found that copper concentration was as much as 60 mg/kg wet weight higher for dairy calves than for beef calves (P Ͻ 0.00001, R 2 ϭ 0.172). For both beef and dairy calves, copper conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Young animals have a greater need for iron and zinc compared to older animals [1, 20]. This may be the biological explication for the higher liver concentrations typically found in young animals compared to older animals [21, 22]. The zinc level steadily drops from birth until 2 years because growing animals need more zinc than non-growing animals [23].…”
Section: Discussionmentioning
confidence: 99%
“…Young animals have a greater need for iron and zinc compared to older animals [1, 20]. This may be the biological explication for the higher liver concentrations typically found in young animals compared to older animals [21, 22]. The zinc level steadily drops from birth until 2 years because growing animals need more zinc than non-growing animals [23].…”
Section: Discussionmentioning
confidence: 99%
“…The mean (SEM) liver copper wet weight concentrations for the placebo, zinc Met, and ZO treated calves were 175.6 (105.6), 143.5 (60.4), and 110.1 (62.0) mg/kg, respectively. It has been reported that newborn calves without clinical signs of copper deficiency or toxicosis can be expected to have liver copper concentrations ranging from 62 to 125 mg/kg wet weight or 190 to 380 mg/kg DW (Puschner et al, 2004b). Calves in the placebo, zinc Met, and ZO treatment groups had mean liver copper DW values higher than this range at exit, indicating that the zinc supplementation did not cause a deficiency in liver copper concentrations.…”
Section: Elisa Status At Enrollmentmentioning
confidence: 97%
“…Contrast myelography showed no compressive lesions of the spinal cord. Concentrations of liver copper were within the reference range 21 (mean ± SD, 226.6 ± 181.6 mg/kg dry matter [DM] basis; range, 95.2–491.7 mg/kg DM) in the calves evaluated. No anticholinesterase activity was detected in the 5 liver samples.…”
Section: Resultsmentioning
confidence: 70%